KAPASITAS PREDASI TUNGAU MACROCHELES MERDATIUS BERLESE (ACARI: MACROCHELIDAE), PADA TELUR LALAT RUMAH MUSCA DOMESTICA LINNAEUS, DI LABORATORIUM - Hartini, Sri; Sigit, Singgih H.; Kadarsan, S.; Koesharto, F.X. (BERITA BIOLOGI, 1998)
The capacity of Macrocheles merdarius Berlese to destroy Musca domestica Unnaeus eggs were related to the mite's development stage. Predation abiality of adult femak M. merdarius on fy eggs was 1.8 egg, followed by deutonymphal stage as much as 1.3 eggs and no predation by the protonymphal stage at all.